1992
DOI: 10.1161/01.hyp.19.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular insulin-like growth factor I increases in early renal hypertension.

Abstract: Increasing interest has been directed toward the possible role of trophically acting molecules as modulators or initiators, or both, of myocardial hypertrophy. The aim of the present study was to investigate the possible role of one such molecule, namely, insulin-like growth factor I, in myocardial hypertrophy developed in response to renal artery stenosis. Two-kidney, one clip Goldblatt hypertension was induced in Wistar rats weighing 180 g, and sham-operated animals were used as controls. Blood pressure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 43 publications
3
51
1
Order By: Relevance
“…27 Moreover, IGF-I has been suggested to be directly involved in cardiac hypertrophy by increasing cardiomyocyte cell size in vitro and by increasing gene expression of myosin light chain-2 and troponin I. 28 In the present study as well as in our previous study on renal hypertensive rats, 7 the left and right ventricles were exposed to identical plasma concentrations of GH, which would imply that the increased myocardial IGF-I expression in response to wall stress was independent of changes in circulating GH levels. Therefore, the finding that RV GH receptor mRNA increased before the expression of IGF-I mRNA is particularly intriguing.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…27 Moreover, IGF-I has been suggested to be directly involved in cardiac hypertrophy by increasing cardiomyocyte cell size in vitro and by increasing gene expression of myosin light chain-2 and troponin I. 28 In the present study as well as in our previous study on renal hypertensive rats, 7 the left and right ventricles were exposed to identical plasma concentrations of GH, which would imply that the increased myocardial IGF-I expression in response to wall stress was independent of changes in circulating GH levels. Therefore, the finding that RV GH receptor mRNA increased before the expression of IGF-I mRNA is particularly intriguing.…”
Section: Discussionmentioning
confidence: 51%
“…7 This was further supported by the finding that IGF-I was more abundant in the subendocardial layers of the left ventricle, where wall stress is highest. Activation of the IGF-I gene appeared to be specific because LV levels of y3-actin mRNA were unchanged in hypertensive rats compared with sham- operated rats.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In models of pressure overload secondary to aortic banding or renal hypertension (17,18), it was shown that IGF-I mRNA expression increased in the myocardium, at an early stage of LV hypertrophy and to a greater extent in the myocardial segments exposed to the highest stress (18,19). Moreover, GHR and IGF-I levels were shown to increase in the right ventricle after induction of volume overload from aorto-caval fistula (19).…”
Section: In Vivo Studiesmentioning
confidence: 99%